2022
DOI: 10.3389/fvets.2022.896270
|View full text |Cite
|
Sign up to set email alerts
|

Silage Fermentation Quality, Anthocyanin Stability, and in vitro Rumen Fermentation Characteristic of Ferrous Sulfate Heptahydrate-Treated Black Cane (Saccharum sinensis R.)

Abstract: Pretreatment of lignocellulose agricultural biomass with iron prior to ensiling is required to accelerate biomass breakdown during fermentation, which could result in functional microorganisms and chemicals that reduce nutrition loss, harmful substances, and improve animal performance. The objective of this study was to investigate the effects of increasing dilutions of ferrous sulfate heptahydrate (FS) pretreatment at fresh matter concentrations of 0, 0.015, and 0.030% on the fermentation quality of black can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 55 publications
3
21
0
Order By: Relevance
“…However, it necessitates a suitable effort prior to ensiling because the breakdown of biomass during anaerobic fermentation results in functional microorganisms and chemicals that reduce nutrient loss in addition to harmful substances ( 1 ). Using iron dilutions can help significantly with forage preservation ( 2 ). These additives can contribute to the retention of nutrients in silage, hence strengthening its feed value and improving the production efficiency of ruminants ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, it necessitates a suitable effort prior to ensiling because the breakdown of biomass during anaerobic fermentation results in functional microorganisms and chemicals that reduce nutrient loss in addition to harmful substances ( 1 ). Using iron dilutions can help significantly with forage preservation ( 2 ). These additives can contribute to the retention of nutrients in silage, hence strengthening its feed value and improving the production efficiency of ruminants ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the highly lignified components of anthocyanin-rich black cane reduce the bioaccessibility of anthocyanin during rumen feeding. In addition, earlier studies demonstrated that the incorporation of anthocyanin-rich black cane with dilutions of FSH at levels ranging from 0.015 to 0.030% on fresh weight (FW) into anthocyanin-rich black cane silages improved the nutritional balance with massively decreased lignin contents, as well as modulated anthocyanin stability during ensiling, and in vitro ruminal fermentation of anthocyanin-rich black cane silages ( 1 , 2 ). These findings support the notion that using those FSH levels might aid the current study in terms of decreasing the lignin content of anthocyanin-rich black cane silages prior to feeding.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations